Kelelahan Kerja pada Pekerja Beberapa Industri Tahu di Desa Kenteng, Bandungan, Semarang - Simanullang, Agnes; Denny, Hanifa; Widjasena, Baju (Jurnal Kesehatan Komunitas, 2025)
Tofu industries in Kenteng Village, Bandungan, Semarang use manual production methods. The subjective complaint of fatigue potentially occurred. The purpose of this study is to analyze several variables that have an influence on worker fatigue in the tofu industry in Kenteng Village, Bandungan, Semarang. This research utilized a quantitative research method and a cross-sectional approach. All 30 workers from three home industries were recruited as the research subjects. Variables in this study were age, years of service, nutritional status, working hours, and physical workload as the independent variables, and work fatigue as the dependent variable. This study operated a chi-square statistical analysis with an alpha (α) at 0.05. This research showed no association between age (p-value: 0.361; α: 0.05 ) and working hours (p-value: 0.269; α: 0.05) on work fatigue. In addition, there is a significant association between the length of work (p-value: 0.019; α: 0.05), nutritional status (p-value: 0.037; α: 0.05), and physical workload (p-value: 0.037; α: 0.05) on work fatigue. It is recommended to implement the rest period regularly, share responsibilities, apply working hours according to labor law, and take several breaks to exercise body stretching.